THE INFLUENCE OF THICKNESS ON THE STRUCTURAL AND OPTICAL PROPERTIES OF ZNO:IN THIN FILMS - Hassan, Najiba Abdullah; Hazaa, Salah Qaduri; Abbas, Abbas Ali (MAGISTRA, 2013)
Indium doped zinc oxide (IZO) thin films were prepared by DC- magnetron sputtering technique on glass at ambient substrates temperature with different thickness. The effect of thickness of films on the structure and optical properties of the films was investigated. The crystal structure and orientation of the films were studded by XRD pattern. All the deposited films are polycrystalline and the dependence of preferred orientation, peak intensities and grain size on the filmâs thicknesses are investigated. The optical absorbance and transmittance through the films was measured spectrophotometrically in the wavelength range 350-900 nm. The absorption coefficient, optical energy gap, Urbach energy, optical constants ( refractive index, extinction coefficient, dielectric constant) and dispersion parameters, such as single-oscillator energy, dispersive energy were determined with different thickness of films and analyzed. Keywords: ZnO:In, Sputtering, Crystal structure, Optical properties